2015
DOI: 10.1007/s11060-014-1710-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of mTORC1 inhibition by everolimus in neurofibromatosis type 2 patients with growing vestibular schwannomas

Abstract: Neurofibromatosis type 2 (NF2) is a genetic disorder with bilateral vestibular schwannomas (VS) as the most frequent manifestation. Merlin, the NF2 tumor suppressor, was identified as a negative regulator of mammalian target of rapamycin complex 1. Pre-clinical data in mice showed that mTORC1 inhibition delayed growth of NF2-schwannomas. We conducted a prospective singleinstitution open-label phase II study to evaluate the effects of everolimus in ten NF2 patients with progressive VS. Drug activity was monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 28 publications
0
71
0
Order By: Relevance
“…Fouladi et al reported what to our knowledge is the only previous single‐agent everolimus trial for pediatric patients with solid tumors, in which everolimus administered daily demonstrated tolerability and mTOR pathway signaling inhibition in PBMCs . Sporadic case reports have described everolimus use for patients with pediatric central nervous system tumors, acute lymphoblastic leukemia, kaposiform hemangioendothelioma, and vestibular schwannomas …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fouladi et al reported what to our knowledge is the only previous single‐agent everolimus trial for pediatric patients with solid tumors, in which everolimus administered daily demonstrated tolerability and mTOR pathway signaling inhibition in PBMCs . Sporadic case reports have described everolimus use for patients with pediatric central nervous system tumors, acute lymphoblastic leukemia, kaposiform hemangioendothelioma, and vestibular schwannomas …”
Section: Discussionmentioning
confidence: 99%
“…23 Sporadic case reports have described everolimus use for patients with pediatric central nervous system tumors, acute lymphoblastic leukemia, kaposiform hemangioendothelioma, and vestibular schwannomas. [26][27][28][29] The COG performed a randomized study of temsirolimus as an mTOR inhibitor or bevacizumab combined with cyclophosphamide and vinorelbine (ARST0921; ClinicalTrials.gov identifier NCT01222715), 15 whereas the ADVL0918 trial (ClinicalTrials.gov identifier NCT01141244) 16 added temsirolimus to a regimen of irinotecan and temozolomide. Despite widespread interest in bevacizumab for adult cancers, to the best of our knowledge its development and indications for pediatric oncology remain uncertain, reflecting its somewhat disappointing responses in children.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the genetic finding of truncation of the one NF2 allele remaining in his tumor, the patient was subsequently started on the mTOR inhibitor, everolimus (10 mg daily). Tumors with defective NF2 function are characterized by constitutive activation of the mTOR pathway and appear to respond to targeted inhibition of the mTOR pathway . Unfortunately, our patient was unable to tolerate everolimus, and developed fatigue with generalized pain, which affected his activities of daily living.…”
Section: Introductionmentioning
confidence: 88%
“…Earlier work by Dr. Vijaya Ramesh’s (Harvard University, MA) laboratory established aberrant activation of mTORC1 signaling in NF2-deficient meningiomas (James et al, 2009; James et al, 2012), which led to clinical trials with the rapamycin analog everolimus for NF2-associated tumors (Goutagny, Giovannini, & Kalamarides, 2017; Goutagny et al, 2015). Further, they showed that the dual mTORC1/mTORC2 inhibitor AZD2014 was more effective than rapamycin in blocking proliferation of meningioma cells.…”
Section: Assessing Therapeutics In Nf2 and Schwannomatosis Through Trmentioning
confidence: 99%
“…Kalamarides, 2017; Goutagny et al, 2015). Further, they showed that the dual mTORC1/mTORC2 inhibitor AZD2014 was more effective than rapamycin in blocking proliferation of meningioma cells.…”
mentioning
confidence: 99%